Strengthening Student's Character through Religious Moderation Education in the Digitalization Era - Putra, Purniadi; Arnadi, Arnadi; Putri, Hadisa (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2024)
The challenges of a heterogeneous society in Indonesia are reducing friction and conflict between adherents of certain religions, adherents, communities, classes, tribes, and groups and creating a peaceful life. Religious moderation is an essential key in reducing extremism and radical acts of religion in Indonesia. The method used is qualitative with a case study approach. The primary data source used is the parents of MIS student Nurul Yaqin Sijang; secondary data sources include school documentation, research journals, and relevant books. Data collection techniques use observation, interviews, and documentation: data analysis techniques, data reduction, data verification, and conclusions. The research results show that parents are essential in shaping their children's understanding of religious moderation. Religious moderation education at home has proven effective in counteracting digitalization's negative influence, often containing radical and extreme content. Parents in border areas, even though they have limited access to technology, still provide a balanced understanding of religion and teach the values of tolerance and empathy between religious believers. This study implies that character education in the digital era must involve the active role of parents in filtering information and providing correct education about religious moderation to avoid polarization and social conflict. This research provides recommendations for policymakers to design educational programs that support the role of parents in religious moderation education in border areas.